(untitled) (City: History, Culture, Society, 2018)
During the nineteenth century socio-political and economic transformations, as well as scientific discoveries, changed views on health and its value. Also, the concept of public health, which was no longer concentrated on the individual but on a group of people, was included in the sphere of interest of the broader strata of society in the Central and Eastern Europe. The hygienic movement occupied an important modernizing segment in a wide range of social movement and had an influence on changes in urban space during the nineteenth and the twentieth centuries. Cleanliness and health became signs of modern city and civilization. More noticeable public interest to hygienic ideas in Lviv emerged in the late nineteenth-early twentieth century. One of the manifestations of this was the emergence of hygienic periodicals that focused on issues of public health issues, and especially hygiene, covered almost all areas of everyday life – hygiene of clothing, nutrition, school an urban hygiene etc. At the first time, such journal was published in Lviv during 1872. Four periodicals dedicated to hygiene were published in the city in the period between 1902 and 1914. The publishing of all these periodicals was a non-profit enterprise, and editors were constantly looking for financial resources to ensure their existence. In the first place, the initiative of publishing belonged to Ukrainian and Polish doctors. Lviv hygienic periodicals were published in Polish and Ukrainian and were addressed to the respective national communities. They discussed the same issues, spread the same ideas, but focused mostly on Polish or Ukrainian readers, reflected the socio-political ideas of that time and integrated the concept of health into the competitive ideas of national development.